Women’s Empowerment in the Birds of Prey Movie (2020) - Putri, Arina; Br.Perangin-angin, Alemina; Putri, Dian Marisha (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This study examines the representation of women's empowerment in Birds of Prey (2020), directed by Cathy Yan. It focuses on the narrative development of the central female characters Harley Quinn, Black Canary, Huntress, and Renee Montoya as they navigate processes of self-assertion, autonomy, and resistance. Employing a qualitative methodology through thematic analysis, the research applies Naila Kabeer’s empowerment framework, which conceptualizes empowerment through three interconnected dimensions: resources, agency, and achievements. The analysis reveals that each protagonist experiences empowerment through distinct personal trajectories. Harley Quinn reclaims her independence following her separation from the Joker. Black Canary asserts her voice and defends others against systemic violence. Huntress converts past trauma into a source of strength. Renee Montoya rejects institutional constraints to act in alignment with her ethical convictions. The film underscores the transformative power of female solidarity and emphasizes that empowerment is a multifaceted construct, expressed through diverse forms of strength, independence, and resilience.